Patterns of belief and action : measurement of student political activism - Sutherland, S. L. (Sharon Lynn), 1940- (University of Toronto Press, 1981)
This study makes a significant contribution to the field of attitude-behaviour research and studies of political radicalism and will be of particular interest to sociologists and social and political psychologists.